2007
DOI: 10.3144/expresspolymlett.2007.51
|View full text |Cite
|
Sign up to set email alerts
|

Performance of epoxy-nanocomposite under corrosive environment

Abstract: Abstract. Nanocomposite materials consisting of polymeric matrix materials and natural or synthetic layered minerals like clay are currently an expanding field of study because these new materials often exhibit a wide range of improved properties over their unmodified starting polymers. Epoxy/organoclay nanocomposites have been prepared by intercalating epoxy into the organoclay via direct mixing process. The clay exfoliation was monitored by X-ray diffraction (XRD) and transmission electron microscopy (TEM). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
17
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 15 publications
1
17
0
Order By: Relevance
“…A number of studies have reported reduction in flexural strength of epoxy based nanocomposites due to water absorption. For instance, Abacha et al [31] reported a decrease in flexural strength and modulus of clay/epoxy nanocomposites due to the water absorption. Buehler and Seferis [32] also reported a drop in flexural strength values of carbon fibre/epoxy and glass fibre/epoxy composites as a result of moisture absorption.…”
Section: Effect Of Water Absorption On the Mechanical Properties Of Ementioning
confidence: 98%
“…A number of studies have reported reduction in flexural strength of epoxy based nanocomposites due to water absorption. For instance, Abacha et al [31] reported a decrease in flexural strength and modulus of clay/epoxy nanocomposites due to the water absorption. Buehler and Seferis [32] also reported a drop in flexural strength values of carbon fibre/epoxy and glass fibre/epoxy composites as a result of moisture absorption.…”
Section: Effect Of Water Absorption On the Mechanical Properties Of Ementioning
confidence: 98%
“…In addition, as has been discussed previously in the water absorption section, the tortuous path that was established by the layered silicate reduced the entrance of the water molecules inside the matrix [96][97][98] . There have been many studies that revealed a reduction of mechanical properties of nanocomposites due to the up-take of the water [57,99,100] .…”
Section: Water Absorption Behaviormentioning
confidence: 99%
“…These materials exhibit significant improvement of properties compared to the neat polymers due to the existence of nano-fillers. Epoxy resins have been utilized for many years in numerous applications such as surface coatings, adhesives, electrical engineering, high voltage electrical insulation material, and painting materials due to their unique properties including good chemical resistance, thermal stability, high strength, low shrinkage on curing, good adhesion, and excellent dielectric properties [1][2][3]. Despite the mentioned advantages, application of epoxy resin is limited due to its low thermal conductivity, high coefficient of linear expansion, high cross linking, and poor resistance to crack propagation [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%